IMPROVING VOCABULARY MASTERY OF FIRST GRADERS OF TUNAS HARUM BANGSA ELEMENTARY SCHOOL USING VISUAL IMAGE IN READING COMPREHENSION - Yolanda Lionny Victoria; Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2023)
The descriptive qualitative methodology is used in this study. Using the information gathered from test and post-test procedures, this strategy enables researchers to provide detailed explanations. The goal of the test is to demonstrate how students' vocabulary grows as a result of reading passages from their text books. This has a connection to the ZPD theory, according to which kids "enjoy experiencing the learning process and growing with the aid of others. 45 children from class 1 at Tunas Harum Bangsa Elementary School. The findings indicated that: 1) The first graders at Tunas Harum Bangsa Elementary School can improve their vocabulary mastery through the use of image media; and 2) Aspects of English vocabulary mastery that are emphasized through the use of image media, namely aspects of reading vocabulary and aspects of reciting vocabulary. Keywords: improving vocabulary mastery, elementary school, reading comprehension, image